1999
DOI: 10.1046/j.1365-2567.1999.00771.x
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian granulocyte–macrophage colony‐stimulating factor and some CpG motifs have an effect on the immunogenicity of DNA and subunit vaccines in fish

Abstract: SUMMARYA eukaryotic plasmid DNA carrying the AACGTT CpG motif in its ampR gene is a 'danger' signal for mice and caused an increase in the specific antibody titres of fish and mice after immunization with b-galactosidase (b-gal ). A second pUC-based plasmid, which is inactive in mice and contains the GACGTC CpG motif in its cytomegalovirus (CMV ) promoter, had no effect on antibody responses to b-gal in either fish or mice. A synthetic oligonucleotide, which contains the GACGTT motif, potentiated antibody resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…Although the adjuvant effect of DNA has been demonstrated in goldfish (26), the potential for using CpG DNA as a prophylactic treatment in fish has not been thoroughly investigated. The present work was undertaken to examine whether CpG ODN could induce resistance to viral infections in fish.…”
Section: Discussionmentioning
confidence: 99%
“…Although the adjuvant effect of DNA has been demonstrated in goldfish (26), the potential for using CpG DNA as a prophylactic treatment in fish has not been thoroughly investigated. The present work was undertaken to examine whether CpG ODN could induce resistance to viral infections in fish.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in 'naked' DNA vaccines it is reported that the vaccination is much more e$cient when the plasmid vector for mammalian DNA contains unmethylated CpG motifs (Sato et al, 1996;Klinman et al, 1997). The adjuvant e#ect of DNA has also been shown to work in goldfish (Carassius auratus L.), where plasmids co-injected with a recombinant protein potentiated antibody responses to the protein (Kanellos et al, 1999). Many of the adjuvants used in fish vaccines, and in particular oil-based adjuvants, contribute to good protection, but at the same time they give serious side-e#ects (Midtlyng et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Kanellos et al (1999) reported that plasmids co-injected with a recombinant protein potentiated antibody responses to the protein in goldfish Carassius auratus. Recently, Jørgensen et al (2001a,b) demonstrated that plasmid DNA and synthetic CpG ODN induced production of IFN-like cytokine and IL-1b in Atlantic salmon Salmo salar and rainbow trout Oncorhynchus mykiss leucocytes.…”
Section: Introductionmentioning
confidence: 99%